Parental imprisonment, child victimization and adult problems - Källström, Åsa (European journal of criminology, 2019)
This study addresses, in a Swedish sample, whether exposure to violence and/or crime during childhood, and mental health and/or behaviour problems as an adult, are overrepresented among young men and women who had a parent in prison at some time when they were a child. Results show that almost all the studied types of childhood victimization and adult problems were overrepresented, but verbal victimization, neglect, witnessing violence, Attention Deficit Hyperactivity Disorder (ADHD) and depression were significantly overrepresented. Although the associations between having a parent in prison and childhood victimization as well as having mental health and behaviour problems are weak, these results indicate that it is important for practitioners who meet such children to be aware that they are more likely than other children not only to suffer from mental health and/or behaviour problems but also to have experienced violence and/or neglect.